Control of plugging in bifunctional periodic mesoporous organosilica with imidazolium framework (BFPMO) via stepwise addition of silica precursors1. Issue 12 (28th March 2015) - Karimi, Babak; Khorasani, Mojtaba; Vali, Hojatollah; Luque, Rafael
<x xml:space="preserve">Abstract</x> The synthesis of novel highly ordered plugged or normal bifunctional periodic mesoporous organosilicas (BFPMOs) with variable content of bridged IL-phenyl or -ethyl units has been described.